Development of electrochemical nanoprobe for real-time intracellular measurements of Fe2+ during ferroptosis - Yanmei Ma; Xinhao Li; Weikang Hu; Muyang Ruan; Ming Yang; Lingqian Chang; Hongri Gu; Chengzhi Hu (Microsystems & Nanoengineering)
Abstract Ferroptosis is an iron-dependent form of regulated cell death driven by phospholipid peroxidation and the accumulation of reactive oxygen species (ROS), holding significant importance for therapeutic applications via its induction or inhibition. Accurate detection of intracellular Fe2+ and ROS is essential, as these molecules play essential roles in initiating and propagating ferroptosis. In this study, we present a novel electrochemical nanoprobe for real-time, highly selective detection of intracellular Fe2+. The nanoprobes are prepared by coating gold nanoparticles (AuNPs) and poly(3,4-ethylenedioxythiophene) (PEDOT) onto silicon carbide nanowires (SiC NWs), which are subsequently functionalized with ferrocenyl endoperoxide carboxylic acid (FDCA) and integrated with a liquid metal-filled glass nanopipette. FDCA is specifically synthesized to enable precise electrochemical detection of Fe2+ with high selectivity (0.1 nM to 1 µM) and exceptional specificity. PEDOT and AuNPs can improve electrical conductivity and provide a versatile interface for further FDCA decoration. We use the nanoprobes to evaluate the intracellular change of Fe2+ in MCF-7 breast cancer cells during erastin-induced ferroptosis. We observe a significant increase in intracellular Fe2+ levels in MCF-7 cells undergoing ferroptosis, accompanied by a notable rise in ROS levels. These findings underscore the potential of this nanoprobe to enhance our understanding of the mechanism of ferroptosis in tumor development and as a potential treatment target.